Preliminary checklist of fish species of Sungai Rengai, Kuala Lipis, Pahang, Malaysia - Syed Abu Bakar, Syed Danial; Farinordin, Farah Ayuni; Mohd Izam, Nur Amalina; Ismail, Nor Azliza; Zainul Abidin, Mohammad Kamaruddin; Sharir, Shazana; Mohamad, Azhari; Razali, Nor Bazilah; Zulkipli, Nurfatin (Universiti Teknologi MARA (UiTM), 2023)
This study contributes preliminary data on the fish checklist of Sungai Rengai, Kuala Lipis, Pahang and the fish status reported by IUCN. Sungai Rengai is located southeast of Penjom Goldmine, Kuala Lipis. Specimens were collected using an electro-fisher aided with scoop nets and cast nets. Fish specimens were sorted, identified, measured, and released. Altogether, 48 individuals caught belonged to six families and nine species, with Cyprinidae as the dominant family and Osteochilus vittatus as the most abundant species (14 individuals). The freshwater fish status in Sungai Rengai by referring to the IUCN Red List of Threatened Species was also documented. All species sampled from Sungai Rengai are listed under Least Concern (LC) except Anguilla bicolor, which is Near Threatened (NT). More intensive studies are recommended in the future by covering a wider river area. Biotic and abiotic factors such as water quality, allometric growth pattern and physical water parameters related to the species composition are also suggested to understand the fish diversity of Sungai Rengai further.